High-strength and high-toughness magnetostrictive alloy and preparation method thereof
Patent Information
- Application Number
- CN202411337090.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
但该类合金磁致伸缩性能相对较低,难以实现应用需求的大磁致伸缩系数
[0015] (1) The magnetostrictive value of the magnetostrictive alloy provided by the present invention is 600~1300×10 -6 ; The tensile strength is 750~950MPa, the yield strength is 550~697 MPa, and the elongation at break is 12.5~22%;
Smart Images

Figure CN119307835A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to a high-strength and high-toughness magnetostrictive alloy and a preparation method thereof. Background Art
[0002] Magnetostriction refers to the behavior of a material changing in both length and volume when it is magnetized in an external magnetic field. Magnetostriction can be divided into linear magnetostriction and volume magnetostriction. Linear magnetostriction often manifests itself as different expansion and contraction behaviors of the material in the directions parallel and perpendicular to the magnetic field, while volume magnetostriction exhibits the same expansion and contraction behavior. In practical applications, the magnetostriction coefficient λ is usually used to characterize the quality of the magnetostrictive performance of the material, λ = ΔL / L (L is the original length of the material, ΔL is the change in the sample when the magnetization state changes). Since magnetostrictive behavior can realize the conversion between mechanical energy and electromagnetic energy, it has been widely used in various important devices such as sensors and transducers since its inception. It is a functional material that plays an important role in the defense and civilian fields.
[0003] The most widely used magnetostrictive material is the rare earth-iron based magnetostrictive material Tb with the commercial grade Terfenol-D. x Dy 1-x Fe y (x = 0.27 ~ 0.33, y = 1.90 ~ 2.10), the main component of this material is Laves phase Tb 0.3 Dy 0.7 Fe2 and a small amount of paramagnetic rare earth-rich phase. Terfenol-D has a large magnetostriction coefficient (~2000×10 -6 ) and other excellent properties, but its brittle texture, poor plasticity, poor processability, high raw material cost, etc., limit the application of this material. On this basis, a solid solution phase is generated in the rare earth-iron-based alloy to increase the mechanical properties of the alloy, so as to optimize the magnetostrictive and mechanical properties of the rare earth-iron-based alloy, but since the Laves phase in the alloy is still the main component, the mechanical properties are still poor.
[0004] In addition, Fe-Ga alloy (Galfenol) has a high -6 The high magnetostriction value, relatively good mechanical properties and simple mechanical processing are possible, which further broadens the application range of magnetostrictive materials. The easy magnetization direction of FeGa alloy at room temperature is <100> The crystallographic direction, i.e. the preferred orientation, is <100> direction, the magnetostrictive strain is the largest, so the <100> Preferentially orienting polycrystals or single crystals is the key technology to obtain high-quality FeGa magnetostrictive materials. However, the preparation of single crystals or oriented polycrystals often requires special equipment and relatively complex processes, which also increases the cost of materials to a certain extent.
[0005] Relatively speaking, metal magnetostrictive materials have relatively good mechanical properties, high strength and plasticity. Since they do not contain rare earth elements, their cost is relatively low. However, the magnetostrictive properties of this type of alloy are relatively low, making it difficult to achieve the large magnetostrictive coefficient required by the application.
[0006] Therefore, the development of a new generation of magnetostrictive materials with a large magnetostriction coefficient and excellent mechanical properties is of great significance to broadening the application of smart materials in high-end manufacturing, aerospace, military products and other fields. Summary of the invention
[0007] In order to overcome the above problems, the present invention proposes a high-strength and high-toughness magnetostrictive alloy and a preparation method thereof, wherein the alloy has the following general formula: Fe 70-x Co x Al y Cr z Ni 30-z-y , wherein x, y, z represent the atomic percentage of the corresponding elements, 20≤x≤40, 5≤y≤15, 5≤z≤15. The alloy has both excellent mechanical properties and bulk magnetostrictive effect; and the magnetostrictive alloy does not contain rare earth elements, which significantly reduces the cost of the magnetostrictive alloy, thereby completing the present invention.
[0008] Specifically, the purpose of the present invention is to provide the following aspects:
[0009] In a first aspect, a magnetostrictive alloy is provided, wherein the alloy has the following general formula: Fe 70- x Co x Al y Cr z Ni 30-z-y , where x, y, and z represent the atomic percentages of the corresponding elements, respectively, 20≤x≤40, 5≤y≤15, and 5≤z≤15.
[0010] In a second aspect, a method for preparing a magnetostrictive alloy is provided, the method comprising:
[0011] Step 1, smelting Fe source, Co source, Al source, Cr source and Ni source to obtain a cast alloy ingot;
[0012] Step 2, sequentially subjecting the cast alloy ingot to heat treatment and water quenching to obtain the alloy;
[0013] In step 1, the ratio of the Fe source, Co source, Al source, Cr source and Ni source satisfies Fe 70-x Co x Al y Cr z Ni 30-z-y, where x, y, and z represent the atomic percentages of the corresponding elements, respectively, 20≤x≤40, 5≤y≤15, and 5≤z≤15.
[0014] The beneficial effects of the present invention include:
[0015] (1) The magnetostrictive value of the magnetostrictive alloy provided by the present invention is 600~1300×10 -6 ; The tensile strength is 750~950MPa, the yield strength is 550~697MPa, and the elongation at break is 12.5~22%;
[0016] (2) The magnetostrictive alloy provided by the present invention has both excellent magnetostrictive properties and mechanical properties, and can be subjected to secondary processing such as rolling and forging;
[0017] (3) The magnetostrictive alloy provided by the present invention does not contain rare earth elements, wherein Fe, Co, Al, Cr and Ni elements are all commonly used alloying elements; the magnetostrictive alloy can be prepared by conventional arc smelting and induction melting, which greatly simplifies the production process and significantly reduces the cost of the magnetostrictive alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only used for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work.
[0019] In the attached picture:
[0020] Figure 1 The engineering stress-strain curve of the magnetostrictive alloy prepared in Example 1 is shown;
[0021] Figure 2 The magnetostrictive strain curve of the magnetostrictive alloy prepared in Example 1 is shown;
[0022] Figure 3 The engineering stress-strain curve of the magnetostrictive alloy prepared in Example 2 is shown;
[0023] Figure 4 The magnetostrictive strain curve of the magnetostrictive alloy prepared in Example 2 is shown;
[0024] Figure 5 The engineering stress-strain curve of the magnetostrictive alloy prepared in Example 3 is shown;
[0025] Figure 6The magnetostrictive strain curve of the magnetostrictive alloy prepared in Example 3 is shown;
[0026] Figure 7 The engineering stress-strain curve of the magnetostrictive alloy prepared in Comparative Example 1 is shown;
[0027] Figure 8 The magnetostrictive strain curve of the magnetostrictive alloy prepared in Comparative Example 2 is shown;
[0028] Fig. 9 The EBSD characterization diagram of the magnetostrictive alloy prepared in Example 1 is shown. DETAILED DESCRIPTION
[0029] The following will refer to the attached Figures 1 to 9 Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0030] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0031] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", etc. indicate positions or positional relationships based on the working state of the present invention, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0032] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0033] In one aspect, a magnetostrictive alloy is provided according to the present invention, wherein the alloy has the following general formula: Fe 70- x Co x Al y Cr z Ni 30-z-y , where x, y, and z represent the atomic percentages of the corresponding elements, respectively, 20≤x≤40, 5≤y≤15, and 5≤z≤15. Within this range, the alloy has both excellent mechanical properties and large bulk magnetostrictive properties.
[0034] In the above alloy, in order to obtain a larger magnetostriction value while ensuring good mechanical properties, as a preferred embodiment, its chemical formula is expressed as Fe 70-x Co x Al y Cr z Ni 30-z-y , x, y, z represent the atomic percentage of the corresponding element, 32≤x≤37, 8≤y≤12, 8≤z≤12. For example, x=35, y=10, z=10.
[0035] In the present invention, the alloy mainly includes BCC phase and FCC phase, the volume fraction of BCC phase is 0.12-0.2%, and the balance is FCC phase; for example, the volume fraction of BCC phase is 0.2%, and the balance is FCC phase.
[0036] Among them, the BCC phase provides the necessary guarantee for improving the strength of the alloy during deformation, thereby obtaining excellent mechanical properties; it also fully guarantees that there are no factors that hinder the volume change of the FCC phase during the magnetization process, thereby ultimately obtaining an alloy system with both mechanical properties and bulk magnetostriction.
[0037] According to the present invention, the magnetostriction value of the alloy is 600~1300×10 -6 ; The tensile strength is 750~950MPa, the yield strength is 550~697 MPa, and the elongation at break is 12.5~22%.
[0038] In a second aspect, a method for preparing the alloy according to the first aspect is provided, the method comprising:
[0039] Step 1, smelting Fe source, Co source, Al source, Cr source and Ni source to obtain a cast alloy ingot;
[0040] Step 2: subjecting the cast alloy ingot to heat treatment and water quenching treatment in sequence to obtain the alloy.
[0041] Specifically:
[0042] Step 1: Smelting Fe source, Co source, Al source, Cr source and Ni source to obtain a cast alloy ingot.
[0043] In step 1, the Fe source is Fe, the Co source is Co, the Al source is Al, the Cr source is Cr, and the Ni source is Ni; further, the purity of the Fe source, Co source, Al source, Cr source and Ni source is greater than 99.9%.
[0044] In the present invention, the alloy prepared from Fe source, Co source, Al source, Cr source and Ni source mainly forms a "BCC+FCC" dual-phase structure, and the BCC phase with a smaller volume fraction plays a mechanical strengthening role because it can prevent the dislocation sliding generated in the mechanically softened FCC phase, which makes the alloy have excellent mechanical properties. When it is not within this composition range, the alloy either forms a single phase or forms other phases, and often cannot obtain good mechanical properties.
[0045] Furthermore, the large volume magnetostriction of the alloy can be qualitatively attributed to the compressible properties and magnetic coupling characteristics of the FCC phase. At the same time, the FCC phase has a "non-collinear" state. This discovery originates from the magnetic spin configuration of the Fe-Ni invar alloy. Under this structure, the volume magnetostriction effect can be understood as the increased external field pushing the size and direction of different magnetic moments to the ferromagnetic state under the "non-collinear" structure. The energy valley transitions from a low-spin small volume state to a high-spin large volume state, resulting in a large volume expansion, and when the external magnetic field disappears, the system will quickly return to the initial state, resulting in non-hysteresis characteristics.
[0046] In summary, the alloy system obtains a suitable phase composition ratio through composition regulation. At the same time, due to the mixture of ferromagnetic elements (Fe and Co), antiferromagnetic elements (Cr) and paramagnetic elements (Al and Ni), there are volume differences between different phases due to different magnetization states, thereby obtaining good mechanical properties and a large bulk magnetostrictive effect.
[0047] In step 1, the ratio of the Fe source, Co source, Al source, Cr source and Ni source satisfies Fe 70-x Co x Al y Cr z Ni 30-x-y , wherein x, y, z represent the atomic percentage of the corresponding element, respectively, 20≤x≤40, 5≤y≤15, 5≤z≤15; preferably, 31≤x≤38, 8≤y≤12, 8≤z≤12.
[0048] In step 1, the smelting includes:
[0049] Step 1-1, gas washing;
[0050] Step 1-2, further evacuate to 2×10 -4 Pa or less, at this time, the Fe source, Co source, Al source, Cr source and Ni source are melted by arc heating;
[0051] Step 1-3, reducing the current to 0, naturally cooling to room temperature, and the obtained solidified product is a cast alloy ingot.
[0052] In step 1-1, gas washing is beneficial to avoid oxidation of Fe source, Co source, Al source, Cr source and Ni source in the later smelting process. Preferably, gas washing is performed 1 to 3 times, for example, 3 times. The gas washing includes: vacuuming to 1×10 -1 Pa, and then fill it with inert gas to a pressure of 0.05MPa~0.06Mpa.
[0053] In step 1-2, arc heating is used to cast the Fe source, Co source, Al source, Cr source and Ni source into a dense cast alloy ingot with uniform composition.
[0054] Among them, the parameters of arc heating setting are different for different equipment, but the alloy composition should be fully uniform during the smelting process to meet the requirement of no internal component segregation. Usually, the initial current is set to 30~50A, and then the current is increased to 140~160A to completely melt the Fe source, Co source, Al source, Cr source and Ni source; for example, the initial current is set to 30A, and then the current is increased to 150A to completely melt the Fe source, Co source, Al source, Cr source and Ni source.
[0055] In step 1-2, during smelting, an inert gas is used as a protective gas, which is beneficial to improving the purity of the cast alloy ingot. The inert gas can be any one or more of argon, helium, and neon, preferably argon, which is widely used. The argon does not react chemically with the metal elements, and can ensure that the metal elements will not be burned, with a good protective effect, and a relatively pure and high-quality cast alloy ingot can be obtained.
[0056] In step 1-2, the Fe source, Co source, Al source, Cr source and Ni source are melted by arc heating. Preferably, the melted mixed solution is smelted for 10 to 20 minutes, such as 10 minutes, which is conducive to fully mixing the mixed solution.
[0057] In step 1-2, the Fe source, Co source, Al source, Cr source and Ni source are melted in a vacuum environment, so that the melting process is more stable and less likely to extinguish; and the contamination of the refractory lining by the smelting of various raw materials is avoided.
[0058] According to a preferred embodiment, in step 1-3, the solidified product is turned over, and the above smelting steps 1-1 to 1-3 are repeated to make the composition of the cast alloy ingot uniform, or in other words, to make the smelting complete and eliminate the composition unevenness caused by the different densities of the metal elements under gravity. Generally, the above smelting operation needs to be performed 5 to 7 times in total.
[0059] According to a preferred embodiment, the smelting in step 1 is carried out in a vacuum arc melting furnace, which has less environmental pollution and a more stable smelting process.
[0060] In step 1, before smelting, the surfaces of the Fe source, Co source, Al source, Cr source and Ni source are preferably polished to remove the oxide layer, and then ultrasonically cleaned in a solvent such as acetone, and then dried for use.
[0061] Step 2: subjecting the cast alloy ingot to heat treatment and water quenching treatment in sequence to obtain the alloy.
[0062] In step 2, the gas is pre-washed before the heat treatment, and the pre-washing is performed 1 to 3 times, preferably 3 times, which includes: vacuuming to 5×10 0 Pa, and then introduce protective gas for washing.
[0063] The protective gas may be nitrogen, or any one or more of inert gases such as argon, helium, and neon, preferably nitrogen or argon, which are cheap and readily available.
[0064] In step 2, before heat treatment and after pre-washing, vacuum is drawn to 2×10 -4 Pa, and then an inert gas such as argon is introduced to a pressure of 0.05MPa to 0.06MPa.
[0065] In step 2, the heat treatment includes: heating from room temperature to 800-1200° C. at a heating rate of 1 K / min-50 K / min, and keeping the temperature for 2-12 hours.
[0066] Among them, the phenomenon of uneven composition is inevitable in the smelting process, so the heat treatment process is a solid solution treatment, which is mainly to further homogenize the composition of the cast alloy ingot. If the heat treatment temperature is too low, it is difficult for atoms to migrate, and if the temperature is too high, it will melt, so choosing the right temperature is crucial; heat treatment time is another factor to make the composition of the cast alloy ingot uniform, because atomic migration is not achieved overnight, but a slow movement process, so the heat treatment time should be increased as much as possible, but the homogenization process is not a simple linear relationship, and the longer the time, the higher the cost, so choose the right time. It is appropriate within the above parameter range.
[0067] In a further preferred embodiment, the heat treatment comprises: heating from room temperature to 950-1050° C. at a heating rate of 50 K / min-20 K / min, and keeping the temperature for 2.5-4 h.
[0068] In a further preferred embodiment, the heat treatment comprises: heating from room temperature to 1000° C. at a heating rate of 10 K / min and keeping the temperature for 3 hours.
[0069] According to the present invention, the normal temperature is usually 0-40°C, for example 25°C.
[0070] In step 2, rapid cooling by water quenching will avoid segregation within the alloy and
[0071] Keep the grains as small as possible to improve the mechanical properties of the alloy.
[0072] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0073] Example 1
[0074] (1) Fe, Co, Al, Cr and Ni were polished, then ultrasonically cleaned with acetone, and dried for later use; according to the chemical composition of Fe 35 Co 35 Al 10 Cr 10 Ni 10 36.24 g Fe, 38.238 g Co, 5.002 g Al, 9.639 g Cr and 10.881 g Ni were weighed, and the weighed Fe, Co, Al, Cr and Ni were put into a water-cooled copper mold in a vacuum arc melting furnace as raw materials, and smelted according to the following steps:
[0075] Washing, that is, vacuuming to 1×10 -1 Pa, and then fill with argon gas to a pressure of 0.05MPa, and purge the gas three times; then, the vacuum degree in the vacuum arc melting furnace is evacuated to 2×10 -4 Pa, with argon as the shielding gas, the arc was struck with a current of 30A, then the current was increased to 150A, and the melting was continued for 10 minutes, and then the current was reduced to 0, and the solidified product was obtained by naturally cooling to room temperature;
[0076] (2) turning over the solidified product obtained in step (1) so that the back side faces upward, and repeating the melting operation in step (1);
[0077] (3) turning over the solidified product obtained in step (2) so that the front side faces upward, and repeating the melting operation in step (1);
[0078] (4) turning over the solidified product obtained in step (3) with the back side facing upward, and repeating the melting operation in step (1);
[0079] (5) turning the solidified product obtained in step (4) so that the front side faces upward, and repeating the smelting operation in step (1) to obtain a cast alloy ingot;
[0080] (6) Place the cast alloy ingot in a quartz tube in a tube sealing machine for pre-washing, that is, evacuate to 5×10 0 Pa, and then purge with nitrogen, repeat this step 3 times; then the vacuum degree is evacuated to 2×10 -4 Pa, then introduce argon gas to a pressure of 0.05MPa, seal the quartz tube with a hydrogen-oxygen flame, and perform heat treatment as follows: heat from 25°C to 1000°C at a heating rate of 10K / min, keep warm for 3h, and then water quench to obtain a magnetostrictive alloy.
[0081] The magnetostrictive alloy was tested by cutting a standard tensile specimen using a Shimadzu AG-IS tensile machine with a strain rate of 1.67×10 -3 / s, and the strain value was measured using an Epsilon 3442 extensometer; the sample was cut out using electric spark wire cutting and the surface was polished flat, and then the strain gauge was attached to measure the magnetostriction value of the sample. The strain gauge model is KYOWA, KFNB-2-C9-350-11. The yield strength of the magnetostrictive alloy obtained at room temperature was measured to be 697 MPa, and the elongation at break was 21.5%; Figure 1 The engineering stress-strain curve of the prepared magnetostrictive alloy is shown, and it can be seen that its tensile strength is 939 MPa; Figure 2 The magnetostrictive strain curve of the prepared magnetostrictive alloy is shown. It can be seen that the bulk magnetostriction value is 1269×10 -6 .
[0082] Fig. 9 The EBSD characterization diagram of the prepared magnetostrictive alloy is shown, and it can be seen that the alloy of this system is a FCC+BCC dual-phase structure, in which the volume fraction of the FCC phase is relatively large, which is 99.8%, but there is a BCC phase near the grain boundary, with a volume percentage of only 0.2%, which also provides the necessary guarantee for the improvement of the strength of this type of alloy during the deformation process, thereby obtaining excellent mechanical properties; the smaller BCC phase also fully guarantees that there are no factors that hinder the volume change of the FCC phase during the magnetization process, thereby finally obtaining an alloy system with both mechanical properties and bulk magnetostriction.
[0083] Example 2
[0084] (1) Fe, Co, Al, Cr and Ni were polished, then ultrasonically cleaned with acetone, and dried for later use; according to the chemical composition of Fe 33 Co 37 Al8Cr 12 Ni 10 33.817 g of Fe, 40.007 g of Co, 3.961 g of Al, 11.447 g of Cr and 10.769 g of Ni were weighed, and the weighed Fe, Co, Al, Cr and Ni were put into a water-cooled copper mold in a vacuum arc melting furnace as raw materials, and smelted according to the following steps:
[0085] Washing, that is, vacuuming to 1×10 -1 Pa, and then fill with argon gas to a pressure of 0.05MPa, and purge the gas three times; then, the vacuum degree in the vacuum arc melting furnace is evacuated to 2×10 -4 Pa, with argon as the shielding gas, the arc was struck with a current of 30A, then the current was increased to 150A, and the melting was continued for 15min, and then the current was reduced to 0, and the solidified product was obtained by naturally cooling to room temperature;
[0086] (2) turning over the solidified product obtained in step (1) so that the back side faces upward, and repeating the melting operation in step (1);
[0087] (3) turning over the solidified product obtained in step (2) so that the front side faces upward, and repeating the melting operation in step (1);
[0088] (4) turning over the solidified product obtained in step (3) with the back side facing upward, and repeating the melting operation in step (1);
[0089] (5) turning the solidified product obtained in step (4) so that the front side faces upward, and repeating the smelting operation in step (1) to obtain a cast alloy ingot;
[0090] (6) Place the cast alloy ingot in a quartz tube in a tube sealing machine for pre-washing, that is, evacuate to 5×10 0 Pa, and then purge with nitrogen, repeat this step 3 times; then draw the vacuum degree to 2×10 -4 Pa, then introduce argon gas to a pressure of 0.05MPa, seal the quartz tube with a hydrogen-oxygen flame, and perform heat treatment as follows: heat from 25°C to 1000°C at a heating rate of 10K / min, keep warm for 3h, and then water quench to obtain a magnetostrictive alloy.
[0091] The magnetostrictive alloy was tested by cutting a standard tensile specimen using a Shimadzu AG-IS tensile machine with a strain rate of 1.67×10 -3 / s, and the strain value was measured using an Epsilon 3442 extensometer; the sample was cut out using electric spark wire cutting and the surface was polished flat, and then the strain gauge was attached to measure the magnetostriction value of the sample. The strain gauge model is KYOWA, KFNB-2-C9-350-11. The yield strength of the magnetostrictive alloy obtained at room temperature was measured to be 584 MPa, and the elongation at break was 13.8%; Figure 3 The engineering stress-strain curve of the prepared magnetostrictive alloy is shown, and it can be seen that its tensile strength is 789 MPa; Figure 4 The magnetostrictive strain curve of the prepared magnetostrictive alloy is shown. It can be seen that the bulk magnetostriction value is 913×10 -6 .
[0092] Example 3
[0093] (1) Fe, Co, Al, Cr and Ni were polished, then ultrasonically cleaned with acetone, and dried for later use; according to the chemical composition of Fe 38 Co 32 Al 12 Cr8Ni 10 39.783 g of Fe, 35.349 g of Co, 6.069 g of Al, 7.797 g of Cr and 11.002 g of Ni were weighed, and the weighed Fe, Co, Al, Cr and Ni were put into a water-cooled copper mold in a vacuum arc melting furnace as raw materials, and smelted according to the following steps:
[0094] Washing, that is, vacuuming to 1×10 -1 Pa, and then fill with argon gas to a pressure of 0.05MPa, and purge the gas three times; then, the vacuum degree in the vacuum arc melting furnace is evacuated to 2×10 -4 Pa, using argon as the shielding gas, striking the arc with a current of 30A, then increasing the current to 150A, melting for 15min, then reducing the current to 0, and naturally cooling to room temperature to obtain the solidified product;
[0095] (2) turning over the solidified product obtained in step (1) so that the back side faces upward, and repeating the melting operation in step (1);
[0096] (3) turning over the solidified product obtained in step (2) so that the front side faces upward, and repeating the melting operation in step (1);
[0097] (4) turning over the solidified product obtained in step (3) with the back side facing upward, and repeating the melting operation in step (1);
[0098] (5) turning the solidified product obtained in step (4) so that the front side faces upward, and repeating the smelting operation in step (1) to obtain a cast alloy ingot;
[0099] (6) The as-cast alloy ingot is placed in a quartz tube in a tube sealing machine for pre-washing, that is, vacuuming to 5×10 0 Pa, and then purge with nitrogen, repeat this step 3 times; then the vacuum degree is evacuated to 2×10 -4 Pa, then introduce argon gas to a pressure of 0.05MPa, seal the quartz tube with a hydrogen-oxygen flame, and perform heat treatment as follows: heat from 25°C to 850°C at a heating rate of 10K / min, keep warm for 10h, and then water quench to obtain a magnetostrictive alloy.
[0100] The magnetostrictive alloy was tested by cutting a standard tensile specimen using a Shimadzu AG-IS tensile machine with a strain rate of 1.67×10 -3 / s, and the strain value was measured using an Epsilon 3442 extensometer; the sample was cut out using electric spark wire cutting and the surface was polished flat, and then the strain gauge was attached to measure the magnetostriction value of the sample. The strain gauge model is KYOWA, KFNB-2-C9-350-11. The yield strength of the magnetostrictive alloy obtained at room temperature was measured to be 574MPa, and the elongation at break was 12.7%; Figure 5 The engineering stress-strain curve of the prepared magnetostrictive alloy is shown, and it can be seen that its tensile strength is 751 MPa; Figure 6 The magnetostrictive strain curve of the prepared magnetostrictive alloy is shown. It can be seen that the bulk magnetostriction value is 667×10 -6 .
[0101] Comparative Example 1
[0102] (1) Grind Fe, Co, Al and Cr, then use acetone ultrasonic cleaning, and dry for later use; according to the chemical composition of Fe 35 Co 35 Al 20 Cr 10 38.503 g of Fe, 40.627 g of Co, 10.627 g of Al and 10.241 g of Cr were weighed, and the weighed Fe, Co, Al and Cr were put into a water-cooled copper mold in a vacuum arc melting furnace as raw materials, and smelted according to the following steps:
[0103] Washing, that is, vacuuming to 1×10 -1 Pa, and then fill with argon gas to a pressure of 0.05MPa, and purge the gas three times; then, the vacuum degree in the vacuum arc melting furnace is evacuated to 2×10 -4 Pa, with argon as the shielding gas, the arc was struck with a current of 30A, then the current was increased to 150A, and the melting was continued for 10 minutes, and then the current was reduced to 0, and the solidified product was obtained by naturally cooling to room temperature;
[0104] (2) turning over the solidified product obtained in step (1) so that the back side faces upward, and repeating the melting operation in step (1);
[0105] (3) turning over the solidified product obtained in step (2) so that the front side faces upward, and repeating the melting operation in step (1);
[0106] (4) turning over the solidified product obtained in step (3) with the back side facing upward, and repeating the melting operation in step (1);
[0107] (5) turning the solidified product obtained in step (4) so that the front side faces upward, and repeating the smelting operation in step (1) to obtain a cast alloy ingot;
[0108] (6) The as-cast alloy ingot is placed in a quartz tube in a tube sealing machine for pre-washing, that is, vacuuming to 5×10 0 Pa, and then purge with nitrogen, repeat this step 3 times; then the vacuum degree is evacuated to 2×10 -4 Pa, then introduce argon gas to a pressure of 0.05MPa, seal the quartz tube with a hydrogen-oxygen flame, and perform heat treatment as follows: heat from 25°C to 850°C at a heating rate of 10K / min, keep warm for 10h, and then water quench to obtain a magnetostrictive alloy.
[0109] Figure 7 The engineering stress-strain curve of the prepared magnetostrictive alloy is shown, and it can be seen that the prepared magnetostrictive alloy is very easy to crack, does not have excellent mechanical properties, and cannot meet the actual use requirements.
[0110] Comparative Example 2
[0111] (1) Fe, Co, Al, Cr and Ni are then ultrasonically cleaned with acetone and dried for later use; according to the chemical composition of Fe 20 Co 50 Al 10 Cr 10 Ni 10 Weigh 20.533 g of Fe, 54.162 g of Co, 4.96 g of Al, 9.557 g of Cr and 10.788 g of Ni, put the weighed Fe, Co, Al, Cr and Ni as raw materials into a water-cooled copper mold in a vacuum arc melting furnace, and melt them according to the following steps:
[0112] Washing, that is, vacuuming to 1×10 -1 Pa, and then fill with argon gas to a pressure of 0.05MPa, and purge the gas three times; then, the vacuum degree in the vacuum arc melting furnace is evacuated to 2×10 -4Pa, with argon as the shielding gas, the arc was struck with a current of 30A, then the current was increased to 150A, and the melting was continued for 15mins, and then the current was reduced to 0, and the solidified product was obtained by naturally cooling to room temperature;
[0113] (2) turning over the solidified product obtained in step (1) so that the back side faces upward, and repeating the melting operation in step (1);
[0114] (3) turning over the solidified product obtained in step (2) so that the front side faces upward, and repeating the melting operation in step (1);
[0115] (4) turning over the solidified product obtained in step (3) with the back side facing upward, and repeating the melting operation in step (1);
[0116] (5) turning the solidified product obtained in step (4) so that the front side faces upward, and repeating the smelting operation in step (1) to obtain a cast alloy ingot;
[0117] (6) The as-cast alloy ingot is placed in a quartz tube in a tube sealing machine for pre-washing, that is, vacuuming to 5×10 0 Pa, and then purge with nitrogen, repeat this step 3 times; then the vacuum degree is evacuated to 2×10 -4 Pa, then introduce argon gas to a pressure of 0.05MPa, seal the quartz tube with a hydrogen-oxygen flame, and perform heat treatment as follows: heat from 25°C to 700°C at a heating rate of 10K / min, keep warm for 2h, and then water quench to obtain a magnetostrictive alloy.
[0118] The yield strength of the magnetostrictive alloy produced at room temperature is 654 MPa, the elongation at break is 9.3%; the tensile strength is 831 MPa; Figure 8 The magnetostrictive strain curve of the prepared magnetostrictive alloy is shown in Figure 2. It can be seen that the magnetostrictive value is only 38×10 -6 , and is linear magnetostriction (elongation in the parallel direction, λ ∥ Indicates that the vertical direction is shortened, using λ ⊥ express).
[0119] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.
Claims
1. A magnetostrictive alloy, characterized in that: The alloy has the following general formula: Fe 70-x Co x Al y Cr z Ni 30-z-y , where x, y, and z represent the atomic percentages of the corresponding elements, respectively, 20≤x≤40, 5≤y≤15, and 5≤z≤15.
2. The alloy according to claim 1, characterized in that Preferably, the magnetostriction value of the alloy is 600-1300×10 -6 .
3. The alloy according to claim 1 or 2, characterized in that The tensile strength of the alloy is 750-950 MPa.
4. The alloy according to claim 1 or 2, characterized in that The yield strength of the alloy is 550~697 MPa.
5. The alloy according to claim 1 or 2, characterized in that The elongation at break of the alloy is 12.5-22%.
6. A method for preparing a magnetostrictive alloy, characterized in that: The method comprises: Step 1, smelting Fe source, Co source, Al source, Cr source and Ni source to obtain a cast alloy ingot; Step 2, sequentially subjecting the cast alloy ingot to heat treatment and water quenching treatment to obtain the alloy; In step 1, the ratio of the Fe source, Co source, Al source, Cr source and Ni source satisfies Fe 70-x Co x Al y Cr z Ni 30-z-y , where x, y, and z represent the atomic percentages of the corresponding elements, respectively, 20≤x≤40, 5≤y≤15, and 5≤z≤15.
7. The method according to claim 5, characterized in that 32≤x≤37, 8≤y≤12, 8≤z≤12.
8. The method according to claim 4, characterized in that In step 1, the smelting includes: Step 1-1, gas washing; Step 1-2, vacuum to 2×10 -4 Pa or less, at this time, the Fe source, Co source, Al source, Cr source and Ni source are melted by arc heating; Step 1-3, reducing the current to 0, naturally cooling to room temperature, and obtaining a cast alloy ingot.
9. The method according to claim 4, characterized in that In step 2, the temperature of the heat treatment is 800-1200°C, preferably 950-1050°C.
10. The method according to claim 4, characterized in that In step 2, the heat treatment time is 2 to 12 hours, preferably 2.5 to 4 hours.
Citation Information
Patent Citations
Heat treatment method, polycrystalline sample preparation method and magnetostrictive material
CN112410524A
High-strength and high-toughness iron-based high-entropy alloy and preparation method thereof
CN117467908A
Magnetostrictive materials and methods of making such materials
US5336337A
Ferromagnetic shape-memory alloy
WO2002014565A1
Cited By
Heterostructure-reinforced wide-temperature-range high-strength-and-toughness magnetostrictive multi-principal-element alloy and preparation method and application thereof
CN121250210A